Aplicações das equações diferenciais e integrais no estudo do trabalho e energia da física - VARELA, Mauro Irineu (2022)
This course conclusion work deals with the applications of Differential and Integral Equations in Physics, where the objective is to show through examples how such mathematical tools are applied in the Physics discipline. Methodologically, it used a qualitative approach, using a bibliographic reference where the contribution of numerous authors served as a guide for this study. As a result, it was observed that the subject is of paramount importance for the teaching of Physics, as it serves as a basis for the teaching of Quantum Mechanics, Modern Physics and Solid State Physics.